Zest Based Visualization for Requirements Negotiation - Alharthi, M.; Salim, S.S. (2011)
Win-Win is one of the most common models which help systems stakeholders resolve conflicts during system Requirements Negotiation (RN). Solving conflicts, however, is barely dependent on visualizing the negotiation itself The Zest algorithm was invented to visualize a standard e-mail discussion and demonstrate a concise overview of the discussion to facilitate a more productive one. This research sought to use this algorithm in visualizing the RN process in groupware. We have formulated a conceptual diagram on which to base the design and development process of the groupware for implementing the Zest algorithm. Our implementation of the algorithm has later been enhanced to produce more types of visualizations in relation to RN.